Determining Weight of Cargo Onboard Ship by Means of Optical Fibre Technology Draft Reading - Ivče, Renato; Jurdana, Irena; Mohović, Robert (Promet - Traffic&Transportation, 2012)
The accuracy of measuring mass of loaded or discharged cargo by draft survey mass measuring method varies due to both systematic and accidental errors. The paper analyzes an error of draft readings on the calculated quarter mean draft, displacement based on the calculated quarter mean draft and the final displacement. By analyzing this problem, the authors have reached the conclusion that the influence of an error made in draft readings can be significant, especially on the draft marks amidships. Optical fibre technology has been suggested as a new option for draft readings. In this paper, the authors propose a liquid level optical sensor for measuring the sea level in the sounding pipe. Draft readings obtained by optical sensors will be entered into ships’ navigational system and load master. KEY WORDS: ship’s draft, error of draft readings, optical fibre technology, liquid level optical sensors.